REJUVENATING KNEE JOINT: AN AYURVEDIC CASE REPORT ON KNEE OSTEOARTHRITIS MANAGEMENT (CAHIERS MAGELLANES-NS, 2024)
This case study showed efficacy of Ayurvedic interventions in the treatment of Janu sandhi gata vata (Knee osteoarthritis), where the knee joints showed advanced bilateral osteoarthritic changes radiologically. A 64-year-old patient presented with complaints of pain in both knee joints as well as low back pain. This case was diagnosed as B/L knee osteoarthritis based on the X-ray findings. The patient underwent Panchakarma procedures and Ayurvedic oral medications and got satisfactory results without side effects. The visual analog scale (from 8 to 2), Significant changes were observed in the BREF Scale, ROM (Flexion improved from 90° to 110° in bilateral limbs) and negative bulge test. Justifiable and satisfactory improvement was noted after each follow-up and after 1 year X-ray showed a reduction in the disease as well and further progression of the disease was controlled. After the treatment course, the knee pain was completely resolved during the walking or on rest, this study generates evidence that Janu Sandhigatavata (Knee osteoarthritis) successfully treated with the Ayurvedic treatment principles.